HIV, pathology and epigenetic age acceleration in different human tissues - Steve Horvath; David T. S. Lin; Michael S. Kobor; Joseph A. Zoller; Jonathan W. Said; Susan Morgello; Elyse Singer; William H. Yong; Beth D. Jamieson; Andrew J. Levine (GeroScience, 2022)
Epigenetic clocks based on patterns of DNA methylation have great importance in understanding aging and disease; however, there are basic questions to be resolved in their application. It remains unknown whether epigenetic age acceleration (EAA) within an individual shows strong correlation between different primary tissue sites, the extent to which tissue pathology and clinical illness correlate with EAA in the target organ, and if EAA variability across tissues differs according to sex. Considering the outsized role of age-related illness in Human Immunodeficiency Virus-1 (HIV), these questions were pursued in a sample enriched for tissue from HIV-infected individuals. We used a custom methylation array to generate DNA methylation data from 661 samples representing 11 human tissues (adipose, blood, bone marrow, heart, kidney, liver, lung, lymph node, muscle, spleen and pituitary gland) from 133 clinically characterized, deceased individuals, including 75 infected with HIV. We developed a multimorbidity index based on the clinical disease history. Epigenetic age was moderately correlated across tissues. Blood had the greatest number and degree of correlation, most notably with spleen and bone marrow. However, blood did not correlate with epigenetic age of liver. EAA in liver was weakly correlated with EAA in kidney, adipose, lung and bone marrow. Clinically, hypertension was associated with EAA in several tissues, consistent with the multiorgan impacts of this illness. HIV infection was associated with positive age acceleration in kidney and spleen. Male sex was associated with increased epigenetic acceleration in several tissues. Preliminary evidence indicates that amyotrophic lateral sclerosis is associated with positive EAA in muscle tissue. Finally, greater multimorbidity was associated with greater EAA across all tissues. Blood alone will often fail to detect EAA in other tissues. While hypertension is associated with increased EAA in several tissues, many pathologies are associated with organ-specific age acceleration.

Correction to: A candidate gene study of intermediate histopathological phenotypes in HIV-associated neurocognitive disorders - Andrew J. Levine; Virawudh Soontornniyomkij; Eliezer Masliah; Janet S. Sinsheimer; Sarah S. Ji; Steve Horvath; Elyse J. Singer; Asha Kallianpur; David J. Moore (Journal of NeuroVirology, 2020)

A candidate gene study of intermediate histopathological phenotypes in HIV-associated neurocognitive disorders - Andrew J. Levine; Virawudh Soontornniyomkij; Eliezer Masliah; Janet S. Sinsheimer; Sarah S. Ji; Steve Horvath; Elyse J. Singer; Asha Kallianpur; David J. Moore (Journal of NeuroVirology, 2020)

Progressive brain atrophy in chronically infected and treated HIV+ individuals - Talia M. Nir; Neda Jahanshad; Christopher R. K. Ching; Ronald A. Cohen; Jaroslaw Harezlak; Giovanni Schifitto; Hei Y. Lam; Xue Hua; Jianhui Zhong; Tong Zhu; Michael J. Taylor; Thomas B. Campbell; et al. (Journal of NeuroVirology, 2019)

No reliable gene expression biomarkers of current or impending neurocognitive impairment in peripheral blood monocytes of persons living with HIV - Austin Quach; Steve Horvath; Natasha Nemanim; Dimitrios Vatakis; Mallory D. Witt; Eric N. Miller; Roger Detels; Peter Langfelder; Paul Shapshak; Elyse J. Singer; Andrew J. Levine (Journal of NeuroVirology, 2018)

Effects of social adversity and HIV on subcortical shape and neurocognitive function - April D. Thames; Taylor P. Kuhn; Zanjbeel Mahmood; Robert M. Bilder; Timothy J. Williamson; Elyse J. Singer; Alyssa Arentoft (Brain Imaging and Behavior, 2018)

Brain-specific HIV Nef identified in multiple patients with neurological disease - Susanna L. Lamers; Gary B. Fogel; Enoch S. Liu; Andrew E. Barbier; Christopher W. Rodriguez; Elyse J. Singer; David J. Nolan; Rebecca Rose; Michael S. McGrath (Journal of NeuroVirology, 2018)

Improvements in brain and behavior following eradication of hepatitis C - Taylor Kuhn; Philip Sayegh; Jacob D. Jones; Jason Smith; Manoj K. Sarma; A. Ragin; Elyse J. Singer; M. Albert Thomas; April D. Thames; Steven A. Castellon; Charles H. Hinkin (Journal of NeuroVirology, 2017)

Multilevel analysis of neuropathogenesis of neurocognitive impairment in HIV - Andrew J. Levine; Virawudh Soontornniyomkij; Cristian L. Achim; Eliezer Masliah; Benjamin B. Gelman; Janet S. Sinsheimer; Elyse J. Singer; David J. Moore (Journal of NeuroVirology, 2016)

Accelerated epigenetic aging in brain is associated with pre-mortem HIV-associated neurocognitive disorders - Andrew J. Levine; Austin Quach; David J. Moore; Cristian L. Achim; Virawudh Soontornniyomkij; Eliezer Masliah; Elyse J. Singer; Benjamin Gelman; Natasha Nemanim; Steve Horvath (Journal of NeuroVirology, 2016)

Factors related to HIV-associated neurocognitive impairment differ with age - Gary B. Fogel; Susanna L. Lamers; Andrew J. Levine; Miguel Valdes-Sueiras; Michael S. McGrath; Paul Shapshak; Elyse J. Singer (Journal of NeuroVirology, 2015)

Progressive cerebral injury in the setting of chronic HIV infection and antiretroviral therapy - Assawin Gongvatana; Jaroslaw Harezlak; Steven Buchthal; Eric Daar; Giovanni Schifitto; Thomas Campbell; Michael Taylor; Elyse Singer; Jeffrey Algers; Jianhui Zhong; Mark Brown; Deborah McMahon; et al. (Journal of NeuroVirology, 2013)

Erratum to: Regional areas and widths of the midsagittal corpus callosum among HIV-infected patients on stable antiretroviral therapies - David F. Tate; Mehul Sampat; Jaroslaw Harezlak; Mark Fiecas; Joseph Hogan; Jeffrey Dewey; Daniel McCaffrey; Daniel Branson; Troy Russell; Jared Conley; Michael Taylor; Giovanni Schifitto; et al. (Journal of NeuroVirology, 2011)

Regional areas and widths of the midsagittal corpus callosum among HIV-infected patients on stable antiretroviral therapies - David F. Tate; Mehul Sampat; Jaroslaw Harezlak; Mark Fiecas; Joseph Hogan; Jeffrey Dewey; Daniel McCaffrey; Daniel Branson; Troy Russell; Jared Conley; Michael Taylor; Giavoni Schifitto; et al. (Journal of NeuroVirology, 2011)

Cerebral metabolite abnormalities in human immunodeficiency virus are associated with cortical and subcortical volumes - Ronald A Cohen; Jaroslaw Harezlak; Assawin Gongvatana; Steven Buchthal; Giovanni Schifitto; Uraina Clark; Robert Paul; Michael Taylor; Paul Thompson; David Tate; Jeffery Alger; Mark Brown; et al. (Journal of NeuroVirology, 2010)

Cerebral metabolite abnormalities in human immunodeficiency virus are associated with cortical and subcortical volumes - Ronald A Cohen; Jaroslaw Harezlak; Assawin Gongvatana; Steven Buchthal; Giovanni Schifitto; Uraina Clark; Robert Paul; Michael Taylor; Paul Thompson; David Tate; Jeffery Alger; Mark Brown; et al. (Journal of NeuroVirology, 2010)

Effects of nadir CD4 count and duration of human immunodeficiency virus infection on brain volumes in the highly active antiretroviral therapy era - Ronald A Cohen; Jaroslaw Harezlak; Giovanni Schifitto; George Hana; Uraina Clark; Assawin Gongvatana; Robert Paul; Michael Taylor; Paul Thompson; Jeffery Alger; Mark Brown; Jianhui Zhong; et al. (Journal of NeuroVirology, 2010)

Human immunodeficiency virus type 1 in the central nervous system leads to decreased dopamine in different regions of postmortem human brains - Adarsh M Kumar; JB Fernandez; Elyse J Singer; Deborah Commins; Drenna Waldrop-Valverde; Raymond L Ownby; Mahendra Kumar (Journal of NeuroVirology, 2009)

Cocaine increases human immunodeficiency virus type 1 neuroinvasion through remodeling brain microvascular endothelial cells - Milan Fiala; Amy J Eshleman; John Cashman; Justin Lin; Albert S Lossinsky; Vannina Suarez; Wendy Yang; Jun Zhang; Waldemar Popik; Elyse Singer; Francesco Chiappelli; Eva Carro; et al. (Journal of NeuroVirology, 2005)